Grain Size in the Class I Protostellar System TMC-1A Constrained with ALMA and Very Large Array Observations - Yusuke Aso; Satoshi Ohashi; Hauyu Baobab Liu; Wenrui Xu (The Astrophysical Journal, 2024)
The disk mass and substructure in young stellar objects suggest that planet formation may start at the protostellar stage, through the growth of dust grains. To accurately estimate the grain size at the protostellar stage, we have observed the Class I protostar TMC-1A using the Jansky Very Large Array (VLA) at the Q (7 mm) and Ka (9 mm) bands at a resolution of ∼0.″2 and analyzed archival data of the Atacama Large Millimeter/submillimeter Array (ALMA) at Bands 6 (1.3 mm) and 7 (0.9 mm) that cover the same spatial scale. The VLA images show a compact structure with a size of ∼25 au and a spectral index of ∼2.5. The ALMA images show compact and extended structures with a spectral index of ∼2 at the central ∼40 au region and another index of ∼3.3 in the outer region. Our spectral energy distribution analysis using the observed fluxes at the four bands suggests one branch with a small grain size of ∼0.12 mm and another with a grown grain size of ∼4 mm. We also model polarized dust continuum emission adopting the two grain sizes and compare them with an observational result of TMC-1A, suggesting that the small grain size is preferable to the grown grain size. The small grain size implies gravitational instability in the TMC-1A disk, which is consistent with a spiral-like component recently identified.